The Differential Pattern In Skeletal-dental Age And Duration Of Growth Spurt Based On Chronological Age And Gender Types (A Comparison Study Between Indonesian And Malaysian Children Populations) - Seno Pradopo; Sindy Cornelia Nelwan; Ardianti Maartrina Dewi; Amalia Wimarizky; Achmad Nadian Permana; Syiral Mastura Abdullah; Diana Md Zahid (Indian Journal of Forensic Medicine & Toxicology, 2024)
Volume: 16 No: 1 (page: 1103-1110)